Mahram dan Pembatasan Pernikahan dalam Konteks Hukum Islam: Kajian Tematik Ayat-Ayat Hukum Keluarga - Firdaus Firdaus; Tati Yalina Andiyah; Lidya andita; Saras Ainurrochimah; fajrul hakim; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Mahram is an important issue in Islam because it can influence behavior, halal and haram. Furthermore, mahram is a wise decision of Allah SWT and also the perfection of this religion which regulates every aspect of life. So, it is important for us to know who is included in the list of mahrams and what their rights are. Furthermore, Mahram also touched on the issue of inter-tribal marriages. The question is whether this can be considered contrary to the existence of Mahram. This issue is still debated by many religious experts and many different sectarian groups have emerged and punished each other by prohibiting inter-tribal marriages. In short, the author emphasizes that this problem is not included in the daruriyyat but only in the hajiyyat category. In other words we can say that inter-tribal marriages are permitted in Islam.